Analysis Of Problems Implementing The Internal Quality Assurance Syste - Abdul Latip, Iqbal Fauzie, Hesti Mustika Ati (International Journal of Management, Innovation, and Education, 2022)
This study aims to analyze the implementation of the quality assurance system in vocational schools in the city of Depok. A qualitative approach is used in this study with the case study method. The research was carried out by observing stages through literature studies, interviews, and documentation. Observation and interview guidelines were made to facilitate research. Research respondents, namely school principals and teachers. The results of the research show that the quality assurance system has been implemented well, but there are problems in three aspects, namely curriculum, infrastructure, and public relations. It can be concluded from the research that the implementation of the quality assurance system at vocational schools in the city of Depok has been going well, but the quality assurance found problems with the curriculum, infrastructure and public relations. Thus there is a need for governance in the vocational school environment.